2022
DOI: 10.3389/fgene.2022.900572
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Genetic Diversity and Population Structure of Wheat Landrace Population Conserved at ICARDA Genebank

Abstract: Landraces are considered a valuable source of potential genetic diversity that could be used in the selection process in any plant breeding program. Here, we assembled a population of 600 bread wheat landraces collected from eight different countries, conserved at the ICARDA's genebank, and evaluated the genetic diversity and the population structure of the landraces using single nucleotide polymorphism (SNP) markers. A total of 11,830 high-quality SNPs distributed across the genomes A (40.5%), B (45.9%), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
3
5
0
Order By: Relevance
“…Genetic diversity indices of lupin, based on SNPs, is high among the nine populations sampled across the Peruvian Andes, which is concordant for individuals that are landraces, as reported for other landraces of rye [51], pea [52] , maize [53], rice [54,55], squash [56], bean [57], wheat [58]. The wealth and abundance among tarwi landraces can be explained due to their adaptation to local environments and diversity of grower´s choice [49].…”
Section: Discussionsupporting
confidence: 68%
“…Genetic diversity indices of lupin, based on SNPs, is high among the nine populations sampled across the Peruvian Andes, which is concordant for individuals that are landraces, as reported for other landraces of rye [51], pea [52] , maize [53], rice [54,55], squash [56], bean [57], wheat [58]. The wealth and abundance among tarwi landraces can be explained due to their adaptation to local environments and diversity of grower´s choice [49].…”
Section: Discussionsupporting
confidence: 68%
“…The genetic diversity indices of lupin, based on SNPs, is high among the nine populations sampled across the Peruvian Andes, which is concordant for individuals that are landraces, as reported for other landraces of rye [50], pea [51], maize [52], rice [53,54], squash [55], bean [56], and wheat [57]. The wealth and abundance of tarwi landraces can be explained by their adaptation to local environments and diversity of grower s choice [48].…”
Section: Discussionsupporting
confidence: 68%
“…For example, a low level of gene ow was also reported among the wheat landrace populations of Mediterranean origin [48]. This phenomenon may be due to deployment of newly developed cultivars across multiple countries and the less use of old wheat landraces and locally selected germplasm in breeding programs [49]. AMOVA indicated that most of the genetic variation (67.16%) occurred within subpopulations, con rming the existence of considerable unique variation in subpopulations (Table 4).…”
Section: Population Structure and Relationshipmentioning
confidence: 83%